Eating disorders among men in the context of mental health and socio-cultural gender issues - Mroczkowska, Dorota; Ziółkowska, Beata (Przegląd Krytyczny, 2021)
The paper undertakes the issues of epidemiology, conditions, and treatment of eating disorders in men, which are not widely recognised both in Polish and international research. The text is based on desk research analysis of research reports on eating disorders. Authors discuss the issue of eating disorders in the context of gender, indicating that the clinical picture of them (including the perception of one's own body, the ways and motives for striving for a perfect figure) is mainly related to the stereotypical roles and tasks that society and culture impose on men and women. The empirical material analysis allows us to assume that ED symptoms in men are more often (than in the case of women) related to (self) stigmatisation, diagnosis difficulty, coexistent dimorphic disorders, substance addictions, and more significant physical activity.ty.